The detection of one-roof contact individuals on the tuberculosis infection of primary school students in Yogyakarta Municipality - Sri Wijayamti, Sri Wijayamti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: With the detection of tuberculosis (TB) infection in children means that there are transmitting infection by the lung TB carrier with positive acid fast (AF) sputum. The transmission more frequently occurred in one-roof close contact.Objective: To know the relationship between the TB infection in primary school students and the one-roof family member with positive AF.Material and methods: This study was performed from May 1997 to September 1999 using case-control study design. The subjects of the study were primary school students in Yogyakarta Municipality. The primary schools involved were selected using proportional population random sampling method by the area IPDA. The study was performed by active case finding of one-roof family members with over 2 week successive cough and performing the sputum culture. As the controls were the students who were confirmed not infected by TB after BCG test, matched for their age and sex. The statistical analysis using univariable and the clinical significance of the risk factor was inferred from the confidence interval.Result: One hundred and forty one TB-infected students were assigned as the cases and 189 students not infected by TB were assigned as the controls. The one-roof family members with over 2 week successive cough were found more in the case group than in thecontrol group, with the Odds ratio = 2.83; (95% CI = 1.01-5.611. The one-roof family members with over 2 week successive cough and positive AF sputum were found only 1 person in each group, with the Odds ratio = 1.34; (95% CI = 0.08-21.65); X2 =Ã¯ÂÂ®. 0.04; p = 0.84.Conclusion: There were more one-roof family members with over 2 week successive cough in the case group. The presence of a one-roof family member with over 2 week successive cough and positive AF sputum culture, was not proved statistically and not conclusive clinically but tendency to be conclusive as the risk factor of the incidence of TB infection in children.Keywords: TB in children - BCG test - risk factor - contact person - positive sputum culture